(untitled) (World Bulletin of Public Health, 2025)
This review summarizes contemporary polymeric enteric coating systems used for targeted oral drug delivery. Major polymer classes, technological approaches, and mechanisms of action are analyzed, including methacrylate copolymers, cellulose derivatives, aqueous polymer dispersions, and hybrid systems. Particular attention is paid to colontargeted delivery for inflammatory bowel diseases and colorectal cancer. The review critically evaluates current limitations such as gastrointestinal pH variability, in vitro–in vivo correlation (IVIVC), scalability, and reproducibility. Clear recommendations are provided regarding experimental validation, including dissolution testing, IVIVC development, mechanical integrity assessment, kinetic modeling, and biocompatibility evaluation. The article is intended to meet the expectations of peer reviewers in pharmaceutical and drug-delivery journals.